A Study on Pollinating Insect Diversity in Selected Areas of Pudunagaram Village, Palakkad, Kerala, India - R, Karthika.; K.V, Zeena. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The present study on Pollinating insect diversity of selected areas of Pudunagaram village, Palakkad, Kerala was conducted for a period of six months from January 2022 – June 2022. Two sites were selected which are diverse in habitats; one is Mangode, the home garden where floral plants were cultivated, and the second is Karippode, the forest area with wild plants. Visual observation and hand- picking methods were used for collection. A total of 49 species belonging to 5 orders and 15 families were recorded of which Order Lepidoptera was dominant with 29 species. In site-1 family Nymphalidae and in site-2 Apidae was dominant. The Shannon diversity index study revealed that insect diversity is slightly higher in site-1 (2.313) as compared to site-2(2.25).